Augmenting ACL Repair With Suture Tape Improves Knee Laxity: A Biomechanical Study. Issue 4 (27th April 2023) - He, Jinshen; Kanto, Ryo; Fayed, Aly M.; Price, Taylor M.; DiNenna, Michael A.; Linde, Monica A.; Smolinski, Patrick; van Eck, Carola F.
Background: Anterior cruciate ligament (ACL) repair is an alternative to reconstruction; however, suture tape support may be necessary to achieve adequate outcomes. Purposes: To investigate the influence of suture tape augmentation (STA) of proximal ACL repair on knee kinematics and to evaluate the effect of the 2 flexion angles of suture tape fixation. Study Design: Controlled laboratory study. Methods: Fourteen cadaveric knees were tested using a 6 degrees of freedom robotic testing system under anterior tibial (AT) load, simulated pivot-shift (PS) load, and internal rotation (IR) and external rotation loads. Kinematics and in situ tissue forces were evaluated. Knee states tested were (1) ACL intact, (2) ACL cut, (3) ACL repair with suture only, (4) ACL repair with STA fixed at 0° of knee flexion, and (5) ACL repair with STA fixed at 20° of knee flexion. Results: ACL repair alone did not restore the intact ACL AT translation at 0°, 15°, 30°, or 60° of flexion. Adding suture tape to the repair significantly decreased AT translation at 0°, 15°, and 30° of knee flexion but not to the level of the intact ACL. With PS and IR loadings, only ACL repair with STA fixed at 20° of flexion was not significantly different from the intact state at all knee flexion angles. ACL suture repair had significantly lower in situ forces than the intact ACL with AT, PS, and IR loadings. With AT, PS, and IR loadings, adding suture tape significantly increased the in situ force in the repaired ACL at all knee flexion angles to become closer to that of the intact ACL state. Conclusion: For complete proximal ACL tears, suture repair alone did not restore normal knee laxity or normal ACL in situ force. However, adding suture tape to augment the repair resulted in knee laxity closer to that of the intact ACL. STA with fixation at 20° of knee flexion was superior to fixation with the knee in full extension. Clinical Relevance: The study findings suggest that ACL repair with STA fixed at 20° could be considered in the treatment of femoral sided ACL tears in the appropriate patient population.